Exploring Mandala – Art as a Form of Therapy - Nur Haziyah Amni Raimaini; Zahit, Ross Azura (Trends in Undergraduate Research, 2023)
The declining trend of mental wellbeing among university students is at a concerning rate. Finding ways to curb the issue before it becomes out of hand is the main objective of this study as it assesses the effectiveness of using mandala art as a therapeutic method in lowering the symptoms of depression, anxiety, and stress among the students. Art has been around for thousands of years, and this study tested the claim specifically on mandala art of its effectiveness as the recently emerged method in the field of psychotherapy. This study applied quantitative research through a quasi-experimental method. 72 participants from University Malaysia Sarawak (UNIMAS) were gathered to join the experiment and the participants were administered the Depression, Anxiety, and Stress Scale (DASS-21) before and after Mandala colouring activity. The effectiveness was measured in terms of the pre and post scores of DASS-21 through Wilcoxon Signed-Rank Test using the SPSS v26.0. Results of the research showed a significant difference between the median of the pre-test scores and post-test scores (p<0.005). The findings of this research supported the hypothesis that involving oneself in therapeutic art activity can lower the register of depression, anxiety, and stress symptoms.